Transitory Earnings Opportunities and Educational Scarring of Men - Jósef Sigurdsson (Institute of Labor Economics (IZA), 2023)
Men have fallen behind women in education in developed countries. Why? I study the impact of a transitory increase in the opportunity cost of schooling on men's and women's educational attainment. I exploit a reform in Iceland that lowered income taxes to zero for one year and compare teenagers above and below the compulsory schooling age. This earnings opportunity increased the dropout rate and led to a permanent loss in years of education for young men, but had no effect on the education of women. Male dropouts suffer substantial losses in lifetime earnings, slow career progression, and reduced marriage and fertility outcomes. The results cannot be explained by negative selection of dropouts or low returns to education but can be reconciled by gender differences in nonpecuniary costs of school attendance, myopia, or perceived returns to education. The findings suggest that due to these gender differences, economic booms misallocate young men away from school, entrenching the gender gap in education.
Keywords: H24; I21; I26; J16; J24; 330; educational attainment; opportunity cost; gender gap; labor supply; tax reform